The TOMMORROW study: Design of an Alzheimer's disease delay‐of‐onset clinical trial. Issue 1 (1st January 2019) - Burns, Daniel K.; Chiang, Carl; Welsh‐Bohmer, Kathleen A.; Brannan, Stephen K.; Culp, Meredith; O'Neil, Janet; Runyan, Grant; Harrigan, Patrick; Plassman, Brenda L.; Lutz, Michael; Lai, Eric; Haneline, Stephen; et al.
Abstract: Introduction: Alzheimer's disease (AD) is a continuum with neuropathologies manifesting years before clinical symptoms; thus, AD research is attempting to identify more disease‐modifying approaches to test treatments administered before full disease expression. Designing such trials in cognitively normal elderly individuals poses unique challenges. Methods: The TOMMORROW study was a phase 3 double‐blind, parallel‐group study designed to support qualification of a novel genetic biomarker risk assignment algorithm (BRAA) and to assess efficacy and safety of low‐dose pioglitazone to delay onset of mild cognitive impairment due to AD. Eligible participants were stratified based on the BRAA (using TOMM40 rs 10524523 genotype, Apolipoprotein E genotype, and age), with high‐risk individuals receiving low‐dose pioglitazone or placebo and low‐risk individuals receiving placebo. The primary endpoint was time to the event of mild cognitive impairment due to AD. The primary objectives were to compare the primary endpoint between high‐ and low‐risk placebo groups (for BRAA qualification) and between high‐risk pioglitazone and high‐risk placebo groups (for pioglitazone efficacy). Approximately 300 individuals were also asked to participate in a volumetric magnetic resonance imaging substudy at selected sites. Results: The focus of this paper is on the design of the study; study results will be presented in a separate paper. Discussion: The design of the TOMMORROW study addressed many key challenges to conducting a dual‐objective phase 3 pivotal AD clinical trial in presymptomatic individuals. Experiences from planning and executing the TOMMORROW study may benefit future AD prevention/delay‐of‐onset trials. Highlights: Applied a genetics‐based algorithm to enrich for near‐term risk of mild cognitive impairment due to Alzheimer's disease. Assessed early cognitive decline with a multidomain neuropsychological test battery. Utilized time to mild cognitive impairment due to Alzheimer's disease as study endpoint. Simultaneous evaluation of a biomarker and therapeutic.